2012
DOI: 10.1537/ase.110411
|View full text |Cite
|
Sign up to set email alerts
|

Facial characteristics of the prehistoric and early-modern inhabitants of the Okinawa islands in comparison to the contemporary people of Honshu

Abstract: Modern inhabitants of the Okinawa islands have been supposed to represent a relatively close genealogical connection to the prehistoric Jomon and the indigenous Ainu, when compared with people living on Japan's main island (Honshu). However, several previous studies have also clarified some morphological facial traits discernible between the early-modern Okinawans and the Jomon of Honshu. In the present study, to further evaluate the Jomon-Okinawan relationship, we compared facial forms between skeletal sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 48 publications
5
19
0
Order By: Relevance
“…These characteristics have also been emphasized in several craniometric studies (Hsu, 1948;Ikeda, 1974;Fukase et al, 2012). We observed that the angle of Ac(m)-Se-Prn is larger in Okinawa Islanders than in mainland Japanese but that the nasal prominence (Prn-RP) is not much different between the populations.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These characteristics have also been emphasized in several craniometric studies (Hsu, 1948;Ikeda, 1974;Fukase et al, 2012). We observed that the angle of Ac(m)-Se-Prn is larger in Okinawa Islanders than in mainland Japanese but that the nasal prominence (Prn-RP) is not much different between the populations.…”
Section: Discussionsupporting
confidence: 76%
“…In studies of early modern crania, it has also been reported that the bizygomatic, biorbital, and mandibular breadths are broader in crania from the Okinawa Islands than those from mainland Japanese (Hsu, 1948;Fukase et al, 2012). Therefore, a broad face has generally been considered to be a characteristic of Okinawa Islanders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The craniofacial morphology of ancient and modern people in the Japanese archipelago has been well studied (von Baelz, 1911;Ikeda, 1974;Brace and Nagai, 1982;Hanihara, 1991;Ishida, 1992;Pietrusewsky, 1999;Dodo et al, 2000;Higa et al, 2003;Fukumine et al, 2006;Haneji et al, 2007;Toma et al, 2007;Fukase et al, 2012;Miyazato et al, 2014). Such studies have revealed that craniofacial features, including dental characteristics, show regional differences even within Japan, especially between the mainland Japanese, Ryukyu Islanders, and Ainu.…”
Section: Introductionmentioning
confidence: 99%
“…Fukase et al (2012) have pointed out that the crania of earlymodern Ryukyu Islanders have, on average, a lower facial height, a broader interorbital space, and sagittally more curved nasal bones than those of the modern mainland Japanese. Based on 3-D facial surface images of living subjects, Miyazato et al (2014) have found that the Ryukyuan people have more prominent glabella and nasal roots, as well as lower facial and nasal heights.…”
Section: Introductionmentioning
confidence: 99%